2011
DOI: 10.1093/rheumatology/keq430
|View full text |Cite
|
Sign up to set email alerts
|

Association between nail-fold capillary findings and disease activity in dermatomyositis

Abstract: Our results suggest that changes in nail-fold capillaries reflect disease activity in DM. Furthermore, the differences found in red blood cell velocity may reflect somewhat distinct microcirculation injuries in DM and SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 38 publications
6
69
0
4
Order By: Relevance
“…By using the tilt angle, 20°, between axial and actual velocity directions, the average absolute velocities are found as ~0.67 mm/s and ~0.61 mm/s for arteriole-end and venule-end capillaries, respectively. These results match with the expected values considering the typical RBC average velocity measured with healthy subjects using NVC is around 0.8 mm/s [22]. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…By using the tilt angle, 20°, between axial and actual velocity directions, the average absolute velocities are found as ~0.67 mm/s and ~0.61 mm/s for arteriole-end and venule-end capillaries, respectively. These results match with the expected values considering the typical RBC average velocity measured with healthy subjects using NVC is around 0.8 mm/s [22]. …”
Section: Resultssupporting
confidence: 90%
“…The maximal and minimal detectable velocities are determined by the time interval T , the π-ambiguity and the system phase noise level [21]. Mapping of RBC velocities in human finger cuticle capillaries, which are typically from ~0.3 to 1 mm/s [22], requires relatively long T , i.e. very slow imaging speed (>20 min.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in nail-fold capillaries have been reported to re fl ect disease activity in dermatomyositis [ 32 ] . Thus, periungual capillary changes such as dilated and tortuous blood vessels, areas of atrophy, telangiectasias, central areas of hemorrhages, splinter hemorrhages, and bushy capillary loop formation in the proximal nail fold have been reported [ 30,33 ] .…”
Section: Dermatomyositis-calcinosismentioning
confidence: 99%
“…Further studies suggested that scleroderma pattern observed in patients with SSc is subject to variations in the course of the disease 8,9,10 , and changes in the capillaroscopic patterns were also found in relation to disease activity 4,7,11 . Several studies describe the association between abnormalities in nailfold microvascular array and idiopathic myopathies (IM), often considering together polymyositis (PM) and DM 12,13,14 . Several studies describe the association between abnormalities in nailfold microvascular array and idiopathic myopathies (IM), often considering together polymyositis (PM) and DM 12,13,14 .…”
mentioning
confidence: 99%